Flavonoid dalam Pencegahan Gagal Ginjal Akibat Stres Oksidatif - Muhammad Ashhabul Kahfi Mathar; Ni Made Linawati; Ida Ayu Ika Wahyuniari; I Gusti Ayu Widianti (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2026)
Kidney failure is a growing global health problem, encompassing acute kidney injury and chronic kidney disease (CKD). CKD is a global health problem, and increased reactive oxygen species (ROS) play a major role in the pathogenesis of CKD through kidney inflammation and fibrosis.1 Recent epidemiological studies have linked flavonoid-rich diets to the incidence of kidney disease.2 Flavonoids are plant-derived phenylchroman compounds that comprise various subclasses, such as flavones, flavanols, isoflavones, anthocyanins, flavon-3-ols, and flavanones. Flavonoids are the third largest group of natural compounds after terpenoids and alkaloids and play a role in protecting the body from oxidative stress and inflammation.3 Phenolic compounds such as phenolic acids, flavonoids, and proanthocyanidins are abundant in plants as a defense mechanism against biotic and abiotic stress. Consumption of polyphenol-rich foods, such as fruits, vegetables, grains, spices, and herbs, is known to reduce the risk of various chronic and degenerative diseases associated with oxidative stress.4